Diseño y propuesta de una plantilla latex para la edición de documentos de titulación de la facultad de Ciencias de la Ingeniería y Aplicadas. - Changoluisa Changoluisa, Edison Xavier (2019)
Text composition systems are used in the student and scientific field. These systems allow the user to create, edit and prepare documents. Due to this, its elaboration is governed to diverse formats depending on the framework of work to which they are oriented. In the faculty of Engineering and Applied Sciences, since there is no clearly defined reference framework, qualification documents are prepared based on the personal guidelines of the tutors. Currently, written presentations are still being developed in text editing tools such as Word of Microsoft Write by LibreOffice. However, for the writing of research or scientific documents they are governed by a more technical format for editing. Based on this, Latex allows you to easily create this type of documents since this system has a set of files which allows generating a professional quality writing. This has to do with providing the user with the typographic language formed by commands from the command Tex, Latex is an open source tool capable of converting any type of text into a predetermined format, whether for theses, scientific articles, student articles, etc. It focuses practically on the content without having to worry about the details of the format, it allows structuring equations, mathematical formulas and bibliography. Which provides comfort and makes it useful for use by teachers and future researchers.